Silicon nitride powder as well as surface modification process and application thereof

By covering the magnesium oxide layer on the surface of the silicon nitride powder, the problem of poor wettability of the silicon nitride powder is solved, and the stability of the casting slurry and the performance of the ceramic substrate are improved, ensuring the casting process Continuity and compactness after sintering.

CN119263225APending Publication Date: 2025-01-07SHENZHEN TAOTAO TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411305280.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the casting process, the silicon nitride powder has poor surface wetting, resulting in solvent volatility and bubble layering, making it difficult to prepare a stable casting diaphragm.

Method used

By sequentially covering the Mg supersaturated first magnesium oxide layer and the Mg low-saturated second magnesium oxide layer on the surface of the silicon nitride powder from the inside to the outside, the wetting and sintering assistance of the silicon nitride powder is improved. The agent is uniformly dispersed, and atomic layer deposition process is used to form a magnesium oxide layer.

Benefits of technology

Improve the wetting and sintering properties of silicon nitride powder, ensure the stability and adhesion of casting slurry, reduce cracking and layering during casting, and improve the three-point bending strength of ceramic substrates and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048984970000041
    Figure BDA0005048984970000041
  • Figure BDA0005048984970000061
    Figure BDA0005048984970000061
  • Figure BDA0005048984970000081
    Figure BDA0005048984970000081
Patent Text Reader

Abstract

The invention discloses silicon nitride powder as well as a surface modification process and application thereof, and relates to the technical field of ceramic substrates. The surface-modified silicon nitride powder comprises silicon nitride powder as well as a first magnesium oxide layer and a second magnesium oxide layer which are sequentially coated on the surface of the silicon nitride powder from inside to outside, and the first magnesium oxide layer and the second magnesium oxide layer are formed by surface deposition of a magnesium source and an oxygen source; the molar ratio of Mg to O in the first magnesium oxide layer is greater than 1, and the molar ratio of Mg to O in the second magnesium oxide layer is less than 1. The first magnesium oxide layer coated with Mg and supersaturated is large in adhesion force with the surface of the silicon nitride powder, the stability of the surface-modified silicon nitride powder is guaranteed, the second magnesium oxide layer coated on the surface is a loose magnesium oxide layer, the specific surface area of the surface of the material is increased, the reaction activity is improved, magnesium oxide has good lipophilicity, and the surface of the material is more stable. The adsorption on organic matters is facilitated, so that the wettability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic substrates, and more specifically, to silicon nitride powder and a surface modification process and application thereof. Background Art

[0002] The molding methods of ceramic substrates generally include dry pressing, tape casting, gel molding, injection molding and hot die casting, but for the preparation of ceramic substrates with a thickness of less than 0.5 mm, the molding method is mainly tape casting. Tape casting has high production efficiency, is easy to produce continuously, and is suitable for large-scale industrial production.

[0003] The basic process of tape casting is: powder, solvent, dispersant, binder, plasticizer, etc. are mixed evenly to form slurry, the slurry is vacuum degassed and then formed into a film with smooth surface and uniform thickness through the scraper of the tape casting machine, and the film is dried in various temperature zones on the tape casting machine to form a tape casting film with good toughness. To prepare continuous and stable tape casting films, the tape casting slurry needs to have appropriate shear thinning properties, good dispersion, moderate viscosity and good fluidity.

[0004] Compared with the tape casting of oxide powders, silicon nitride powders have fewer surface hydroxyls, so the solvents, dispersants, binders, etc. in the slurry are less adsorbed on the surface of silicon nitride powders, and they are poorly bonded to each other, which leads to the phenomenon that the solvent in the tape casting slurry is easily volatilized during the tape casting process, which makes the tape casting of silicon nitride difficult. In addition, because the surface of silicon nitride powder is covered with silicon oxide (such as Si2N2O, SiO2), silicon oxide has poor wettability with binders, dispersants, etc., which causes bubbling and stratification of silicon nitride tape casting films during the subsequent lamination pressing process.

[0005] In the prior art, magnesium oxide is often used as a sintering aid and added to the tape casting slurry. The adding methods include: (1) directly mixing magnesium oxide powder with silicon nitride powder; for example, the preparation method of silicon nitride ceramics with adjustable resistivity in patent CN118125834A comprises wet mixing the sintering aid and silicon nitride powder in alcohol, and then drying and sintering the resulting mixed slurry. (2) Dissolve a soluble magnesium salt (such as magnesium nitrate) and mix it with silicon nitride powder, and then convert it into magnesium oxide through heat treatment; such as a photocurable silicon nitride ceramic slurry, silicon nitride ceramic and its preparation method in patent CN108892515A, mix silicon nitride powder solution, sintering aid solution, first dispersant and precipitant to obtain precipitation solution, and then calcine at 500-800°C to obtain coated powder; wherein the sintering aid solution includes one or more of aluminum chloride hexahydrate solution, aluminum nitrate nonahydrate solution, yttrium nitrate hexahydrate solution, magnesium chloride hexahydrate solution and magnesium nitrate hexahydrate solution. The chemical precipitation method of mixing silicon nitride powder solution, sintering aid solution, dispersant and precipitant achieves surface coating of silicon nitride powder, changes the surface properties of silicon nitride powder, and realizes uniform dispersion of sintering aid. However, the above technical means have not been able to effectively improve the wettability of silicon nitride powder and other slurry components, thereby reducing the bubbling and delamination of silicon nitride cast film during the subsequent lamination pressing process. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects and shortcomings of the existing silicon nitride powder, that is, the poor wettability, and to provide a surface-modified silicon nitride powder.

[0007] Another object of the present invention is to provide a surface modification process for silicon nitride powder.

[0008] Another object of the present invention is to provide an application of silicon nitride powder in the preparation of a silicon nitride ceramic substrate.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0010] The present invention protects a surface-modified silicon nitride powder, comprising silicon nitride powder and a first magnesium oxide layer and a second magnesium oxide layer sequentially coated on the surface of the silicon nitride powder from the inside to the outside, wherein the first magnesium oxide layer and the second magnesium oxide layer are formed by surface deposition of a magnesium source and an oxygen source;

[0011] The molar ratio of Mg to O in the first magnesium oxide layer is >1,

[0012] The molar ratio of Mg to O in the second magnesium oxide layer is less than 1.

[0013] The surface-modified silicon nitride powder of the present invention has a first magnesium oxide layer with supersaturated Mg coated on the surface of the silicon nitride powder, which can remove silicon oxides covering the surface of the silicon nitride powder and has a strong bonding force with the surface of the silicon nitride powder; meanwhile, a second magnesium oxide layer with low Mg saturation is coated on the outer side of the first magnesium oxide layer, and a loose magnesium oxide layer is formed when the Mg saturation is low and the O source is sufficient, thereby increasing the specific surface area of ​​the material surface and the reaction activity, and the magnesium oxide has good lipophilicity, which is conducive to the adsorption of organic matter, thereby improving the wettability.

[0014] Specifically, the first magnesium oxide layer is supersaturated with Mg. Since the activity of metallic magnesium is greater than that of silicon, the affinity of magnesium for oxygen is much higher than that of silicon for oxygen, resulting in the transfer of oxygen of silicon oxide on the surface of silicon nitride particles to the magnesium metal layer under the adsorption of magnesium, and in the case of insufficient oxygen source, partial magnesium oxide is formed, which can improve the adhesion to the surface of silicon nitride powder. At the same time, the direct contact interface between silicon nitride and magnesium metal is oxygen-free, avoiding the problem of increased lattice oxygen in silicon nitride. In addition, partially oxidized metallic magnesium can be used as a sintering aid during the sintering process of silicon nitride powder, and the other part of the unoxidized metallic magnesium forms a liquid phase of magnesium and magnesium oxide at the initial stage of sintering, which is helpful for material transfer and reaction during the sintering process and promotes the densification of silicon nitride ceramic substrates.

[0015] In some embodiments, the molar ratio of Mg to O in the first magnesium oxide layer is (5-10):3.

[0016] In some embodiments, the molar ratio of Mg to O in the second magnesium oxide layer is 3:(5-10).

[0017] In some embodiments, the surface deposition is atomic layer deposition (ALD) and / or chemical vapor deposition (CVD).

[0018] The present invention provides a surface modification process for silicon nitride powder, comprising the following steps:

[0019] S1, performing an atomic layer deposition on silicon nitride powder, and depositing a first magnesium oxide layer on the surface of the silicon nitride powder;

[0020] The step of atomic layer deposition comprises: pulsing a magnesium source precursor for (5-10) n seconds and then purging with an inert gas, pulsing an oxygen source precursor for 3 n seconds and then purging with an inert gas, and repeating the above steps for cyclic deposition; wherein n is a real number, and n≥1;

[0021] S2, performing secondary atomic layer deposition on the powder obtained in step S1 to form a second magnesium oxide layer, thereby obtaining surface-modified silicon nitride powder;

[0022] The steps of secondary atomic layer deposition include: pulsing a magnesium source precursor 3m times and then purging with an inert gas, pulsing an oxygen source precursor (5 to 10)m times and then purging with an inert gas, and repeating the above steps for cyclic deposition; wherein m is a real number, and m≥1.

[0023] In some embodiments, 1≤n≤3; preferably, 1≤n≤2.

[0024] In some embodiments, 1≤m≤3; preferably, 1≤m≤2.

[0025] The present invention has no special requirements on the thickness of the magnesium oxide layer; preferably, the thickness of the second magnesium oxide layer is greater than the thickness of the first magnesium oxide layer, and the total thickness of the two magnesium oxide layers is ≤40nm.

[0026] In some embodiments, the atomic layer deposition cycle is 10-40.

[0027] In some embodiments, the thickness of the first magnesium oxide layer is 1.2-6 nm.

[0028] In some embodiments, the secondary atomic layer deposition has a cycle period of 45-70.

[0029] In some embodiments, the second magnesium oxide layer has a thickness of 5.4-10.5 nm.

[0030] In some embodiments, in step S1, the silicon nitride powder is further pretreated before the atomic layer deposition, and the pretreatment is heating at 95-130° C. for 1.5-5 hours.

[0031] In some of the embodiments, the parameters of the atomic layer deposition are: deposition temperature of 150-200° C., and carrier gas flow rate of 30-50 sccm.

[0032] In some embodiments, the parameters of the secondary atomic layer deposition are: deposition temperature 80-150° C., and carrier gas flow rate 30-50 sccm.

[0033] In some embodiments, the magnesium source precursor is dicyclopentadienylmagnesium (Mg(Cp)2) and / or trimethylmagnesium.

[0034] In some embodiments, the oxygen source precursor is H2O and / or O3.

[0035] In some embodiments, during the atomic layer deposition of step S1, a hafnium source precursor is pulsed into the silicon nitride powder before the magnesium source precursor is pulsed, and the pulse time of the hafnium source is 0.2-2s. The hafnium source precursor is tetrakis(ethylmethylamino)hafnium (Hf(NEtMe)4), and doping with Hf atoms is beneficial to improving the bonding force between magnesium atoms and the silicon nitride surface.

[0036] In some embodiments, during the secondary atomic layer deposition process of step S2, ammonia gas is pulsed before the oxygen source precursor is pulsed, and the pulse time of ammonia gas is 0.1-1 s. Pulsing ammonia gas can inhibit the adsorption and reaction of the oxygen source to a certain extent.

[0037] In some embodiments, when the magnesium source precursor is pulsed continuously, ozone is pulsed between adjacent magnesium source precursor pulses, and the pulse time of the ozone is 0.1-1 s. Pulsing ozone between Mg-Mg atomic layers can activate the surface of Mg atoms, thereby increasing the subsequent reaction attachment sites of Mg.

[0038] The present invention protects the use of a surface-modified silicon nitride powder or a product made by a surface modification process of the surface-modified silicon nitride powder in the preparation of a silicon nitride ceramic substrate.

[0039] In some of the embodiments, the preparation process is as follows: silicon nitride powder is mixed with a dispersant, a binder, a plasticizer and a solvent to form a tape casting slurry, tape casting is performed to form a film, lamination, vacuum encapsulation, warm isostatic pressing, debinding, and sintering to obtain the product.

[0040] In some embodiments, the casting slurry includes the following components in parts by weight:

[0041]

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention provides a surface-modified silicon nitride powder, wherein the surface of the silicon nitride powder is sequentially coated with a first magnesium oxide layer and a second magnesium oxide layer from the inside to the outside. The surface of the silicon nitride powder is coated with the first magnesium oxide layer with Mg supersaturation, which can remove the silicon oxide covered on the surface of the silicon nitride powder, and has a strong bonding force with the surface of the silicon nitride powder, thereby ensuring the stability of the surface-modified silicon nitride powder; the second magnesium oxide layer formed when Mg is low-saturated and the O source is sufficient is a loose magnesium oxide layer, which increases the specific surface area of ​​the material surface and improves the reaction activity, and magnesium oxide has good lipophilicity, which is conducive to the adsorption of organic matter, thereby improving wettability. The tape casting slurry prepared by the silicon nitride powder has high adhesion during the layering process, and there is no cracking in the tape casting process and no stratification after pressing. In addition, after coating with two layers of magnesium oxide layers, the silicon nitride powder is not easy to agglomerate, and the tape casting slurry process is easy to disperse, and the performance of the obtained ceramic product will also be more stable. The silicon nitride ceramics prepared by tape casting of modified silicon nitride powder have a three-point bending strength of over 802 MPa and a thermal conductivity of over 85.8 W / (m·K). DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0045] Examples 1-10

[0046] A surface modification process for silicon nitride powder comprises the following steps:

[0047] S1, pretreatment: heat treatment of silicon nitride powder with an average particle size of 1 μm to remove adsorbed water, dust or other pollutants in the silicon nitride powder;

[0048] S2, performing an atomic layer deposition on the silicon nitride powder, and depositing a first magnesium oxide layer on the surface of the silicon nitride powder;

[0049] The steps of the atomic layer deposition include: pulsing a hafnium source precursor for a second, pulsing a magnesium source precursor for nX1 seconds (X1>3), and then purging with an inert gas, and adding an ozone (O3) pulse for b seconds between every 3n seconds of the magnesium source precursor pulse;

[0050] Before pulsing the oxygen source precursor, ammonia (NH3) is pulsed for c seconds, and then the oxygen source precursor is pulsed for nY1 seconds (Y1≥3) and then purged with inert gas, and the above steps are repeated cyclically to deposit to a preset thickness;

[0051] S3, performing secondary atomic layer deposition on the powder obtained in step S2 to form a second magnesium oxide layer, thereby obtaining surface-modified silicon nitride powder;

[0052] The steps of secondary atomic layer deposition include: pulsing a magnesium source precursor mX2 (X2≥3) followed by an inert gas purge, pulsing an oxygen source precursor mY2 (Y1>3) followed by an inert gas purge, and repeating the above steps to cyclically deposit to a preset thickness.

[0053] Wherein, n=m=1, and X1, X2, Y1, Y2, a, b and c are shown in Table 1.

[0054] The magnesium source precursor is dicyclopentadienyl magnesium; the oxygen source precursor is H2O, and the hafnium source precursor is tetrakis(ethylmethylamino)hafnium (Hf(NEtMe)4).

[0055] The parameter conditions of this embodiment are:

[0056] Atomic layer deposition once: carrier gas flow rate is 40 sccm, and the purge time of each inert gas (nitrogen) is 15 s;

[0057] Secondary atomic layer deposition: The carrier gas flow rate was 40 sccm, and the inert gas (nitrogen) purge time was 15 s each time.

[0058] The parameter conditions of Examples 1-10 are shown in Table 1.

[0059] Table 1

[0060]

[0061] Embodiment 11

[0062] A method for preparing a silicon nitride ceramic substrate, wherein the silicon nitride powder obtained by the surface modification process of Example 1 is prepared into a tape casting slurry, wherein the slurry composition is as follows: modified silicon nitride powder, rare earth oxide Y2O3, BYK as a dispersant, anhydrous ethanol and toluene as a solvent, PVB as a binder and a plasticizer DOP; the particle size of the tape casting slurry is 0.6 μm, and the viscosity is 8000 mPa.s;

[0063] The slurry formula is as follows by mass percentage:

[0064] Modified silicon nitride powder: 55%,

[0065] Y2O3: 1.2%,

[0066] BKY: 0.8%,

[0067] Anhydrous ethanol: 17%,

[0068] Toluene: 17%,

[0069] PVB: 5%,

[0070] DOP: 4%.

[0071] The casting slurry is cast to form a casting film, and the casting process is as follows: temperature is 45° C., air intake is 5%, air exhaust is 10%, film thickness is 0.15 mm, and speed is 2 m / min.

[0072] The cast film is laminated, vacuum-encapsulated, and warm isostatically pressed. After debinding at 600°C, it is transferred to a gas pressure furnace for sintering (1750°C for 8 hours, with high-purity nitrogen as the protective gas and a nitrogen pressure of 2MPa) to obtain a silicon nitride ceramic substrate.

[0073] Comparative Example 1

[0074] A processing process for silicon nitride powder, which is different from Example 1 in that: the silicon nitride of this comparative example

[0075] The surface modification process of the powder includes the following steps:

[0076] S1, pretreatment: heat treatment of silicon nitride powder to remove adsorbed water, dust or other pollutants in the silicon nitride powder;

[0077] S2, performing atomic layer deposition on silicon nitride powder, and depositing a magnesium oxide layer on the surface of the silicon nitride powder;

[0078] The atomic layer deposition step includes: pulsing a magnesium source precursor for 9 seconds and then purging with an inert gas, pulsing an oxygen source precursor for 3 seconds and then purging with an inert gas, and repeating the above steps for periodic cyclic deposition to obtain surface-modified silicon nitride powder.

[0079] Comparative Example 2

[0080] A processing process for silicon nitride powder, which is different from Example 1 in that: the silicon nitride of this comparative example

[0081] The surface modification process of the powder includes the following steps:

[0082] S1, pretreatment: heat treatment of silicon nitride powder to remove adsorbed water, dust or other pollutants in the silicon nitride powder;

[0083] S2, performing atomic layer deposition on the powder to form a magnesium oxide layer, thereby obtaining surface-modified silicon nitride powder;

[0084] The atomic layer deposition step includes: pulsing a magnesium source precursor for 3 seconds and then purging with an inert gas, pulsing an oxygen source precursor for 9 seconds and then purging with an inert gas, and repeating the above steps for cyclic deposition.

[0085] Comparative Example 3

[0086] A method for preparing a silicon nitride ceramic substrate comprises the following steps:

[0087] (1) Silicon nitride powder with an average particle size of 1 μm was heat treated at 100°C for 4 hours to remove water, dust or other pollutants adsorbed in the silicon nitride powder.

[0088] (2) preparing a tape-casting slurry from the silicon nitride powder obtained in step (1), wherein the tape-casting slurry has a particle size of 0.6 μm and a viscosity of 8000 mPa.s;

[0089] (3) The casting slurry is cast into a casting film, and the casting process is as follows: temperature is 45° C., air intake is 5%, air exhaust is 10%, film thickness is 0.15 mm, and speed is 2 m / min.

[0090] (4) The cast film is sequentially laminated, vacuum-encapsulated, warm isostatically pressed, and sintered at 1800° C. to obtain a silicon nitride ceramic substrate.

[0091] Performance Testing

[0092] The silicon nitride ceramic substrates were prepared from the silicon nitride powders of Examples 1-10 and Comparative Examples 1-2 using the preparation method of Example 11, with a sintering temperature of 1750-1800°C. The performance of the silicon nitride ceramic substrates prepared above and the silicon nitride ceramic substrate of Comparative Example 3 were tested, and the results are shown in Table 2.

[0093] Three-point bending strength: tested according to the method of standard GB / T 6569-2006.

[0094] Thermal conductivity: tested according to the method of standard GB / T 5598-2015.

[0095] The degree of cracking of the cast film is graded and evaluated through macroscopic observation. The evaluation grades are: severe cracking (maximum crack width is more than 1 mm) -, cracking (cracks are still visible after mutual squeezing) -, slight cracking (cracks are not visible after mutual squeezing) 0, no cracking +.

[0096] Table 2

[0097]

[0098]

[0099] It can be seen from Table 2 that the silicon nitride powder obtained by the surface modification process of the present invention can effectively absorb organic matter in the casting slurry and has good wettability, so that the casting slurry has high adhesion during the lamination process, there is no cracking during the casting process, no delamination after pressing, the three-point bending strength reaches more than 802 MPa, and the thermal conductivity reaches more than 85.8 W / (m·K).

[0100] In Comparative Example 1, the surface of the silicon nitride powder is a magnesium oxide layer with high saturation adsorption of Mg, which fails to effectively increase the wettability with the organic matter in the casting slurry. The cast film is severely cracked and severely delaminated after pressing, and the three-point bending strength and thermal conductivity are low.

[0101] In Comparative Example 2, the surface of the silicon nitride powder is a magnesium oxide layer with low saturation adsorption of Mg, which increases the wettability between the powder and the organic matter in the casting slurry to a certain extent. However, the bonding strength between the magnesium oxide layer and the silicon nitride powder particles is low and the stability is poor. Although it can greatly reduce the degree of cracking of the cast film, the stratification is serious after pressing, and its three-point bending strength and thermal conductivity are low.

[0102] In Comparative Example 3, the silicon nitride powder was not subjected to surface modification treatment, and the cast film prepared by the cast film was severely cracked, severely delaminated after pressing, and had low three-point bending strength and thermal conductivity.

[0103] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A surface-modified silicon nitride powder, characterized in that: It comprises silicon nitride powder and a first magnesium oxide layer and a second magnesium oxide layer sequentially coated on the surface of the silicon nitride powder from the inside to the outside, wherein the first magnesium oxide layer and the second magnesium oxide layer are formed by surface deposition of a magnesium source and an oxygen source; The molar ratio of Mg to O in the first magnesium oxide layer is >1, The molar ratio of Mg to O in the second magnesium oxide layer is less than 1.

2. The surface-modified silicon nitride powder according to claim 1, characterized in that: The molar ratio of Mg to O in the first magnesium oxide layer is (5-10):

3.

3. The surface-modified silicon nitride powder according to claim 1, characterized in that: The molar ratio of Mg to O in the second magnesium oxide layer is 3:(5-10).

4. A surface modification process for silicon nitride powder, characterized in that: The following steps are involved: S1, performing an atomic layer deposition on silicon nitride powder, and depositing a first magnesium oxide layer on the surface of the silicon nitride powder; The step of atomic layer deposition comprises: pulsing a magnesium source precursor (5-10) n seconds and then purging with an inert gas, pulsing an oxygen source precursor (3n seconds) and then purging with an inert gas, and repeating the above steps for cyclic deposition; wherein n is a real number, and n≥1; S2, performing secondary atomic layer deposition on the powder obtained in step S1 to form a second magnesium oxide layer, thereby obtaining surface-modified silicon nitride powder; The steps of secondary atomic layer deposition include: pulsing a magnesium source precursor for 3 milliseconds and then purging with an inert gas, pulsing an oxygen source precursor for (5 to 10) milliseconds and then purging with an inert gas, and repeating the above steps for cyclic deposition; wherein m is a real number, and m≥1.

5. The surface modification process of the surface-modified silicon nitride powder according to claim 4, characterized in that: The parameters of the atomic layer deposition are: deposition temperature 150-200° C., carrier gas flow rate 30-50 sccm.

6. The surface modification process of the surface-modified silicon nitride powder according to claim 4, characterized in that: The parameters of the secondary atomic layer deposition are: deposition temperature 80-150° C., carrier gas flow rate 30-50 sccm.

7. The surface modification process of the surface-modified silicon nitride powder according to claim 4, characterized in that: During the atomic layer deposition process of step S1, a hafnium source precursor is pulsed into the silicon nitride powder before a magnesium source precursor is pulsed, and the pulse time of the hafnium source precursor is 0.2-2s.

8. The surface modification process of the surface-modified silicon nitride powder according to claim 4, characterized in that: During the secondary atomic layer deposition of step S2, ammonia gas is pulsed before the oxygen source precursor is pulsed, and the pulse time of the ammonia gas is 0.1-1 s.

9. The surface modification process of the surface-modified silicon nitride powder according to claim 4, characterized in that: When the magnesium source precursor is pulsed continuously, ozone is pulsed between adjacent pulses, and the pulse time of the ozone is 0.1-1 s.

10. Use of a product obtained by a surface modification process of the surface-modified silicon nitride powder according to any one of claims 1 to 3 or the surface-modified silicon nitride powder according to any one of claims 4 to 9 in the preparation of a silicon nitride ceramic substrate.

Citation Information

Patent Citations

  • Photo-cured silicon nitride ceramic slurry, silicon nitride ceramic and preparation method thereof

    CN108892515A